1987
DOI: 10.1021/bi00394a041
|View full text |Cite
|
Sign up to set email alerts
|

Excess zinc ions are a competitive inhibitor for carboxypeptidase A

Abstract: The mechanism for inhibition of enzyme activity by excess zinc ions has been studied by kinetic and equilibrium dialysis methods at pH 8.2, I = 0.5 M. With carboxypeptidase A (bovine pancreas), peptide (carbobenzoxyglycyl-L-phenylalanine and hippuryl-L-phenylalanine) and ester (hippuryl-L-phenyl lactate) substrates were inhibited competitively by excess zinc ions. The Ki values for excess zinc ions with carboxypeptidase A at pH 8.2 are all similar [Ki = (5.2-2.6) X 10(-5) M]. The apparent constant for dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…7C). This biphasic property is observed in other Zn 2ϩ -dependent enzymes (34,35). Zinc carboxypeptidases are inhibited by divalent cation chelators (36,37), and both EDTA and OP, inhibitors of zinc carboxypeptidases (37,38), reduce the activity of Nna1 (Fig.…”
Section: Purified Recombinant Nna1 Is Activated By Zinc and Inhibitedmentioning
confidence: 57%
“…7C). This biphasic property is observed in other Zn 2ϩ -dependent enzymes (34,35). Zinc carboxypeptidases are inhibited by divalent cation chelators (36,37), and both EDTA and OP, inhibitors of zinc carboxypeptidases (37,38), reduce the activity of Nna1 (Fig.…”
Section: Purified Recombinant Nna1 Is Activated By Zinc and Inhibitedmentioning
confidence: 57%
“…The fact that endopeptidase 24.16 was blocked by zinc while the most potent inhibitor agent was a-phenanthroline suggested that renal endopeptidase 24.16 belongs to the zinc-metallopeptidase family, in agreement with our previous data showing that the intestinal apoenzyme could be eficiently reactivated by low concentrations of zinc (Barelli et al, 1988). The dual activating and inactivating effect of zinc ions was previously reported for various zinc-containing metalloenzymes and was recently examined by Hirose et al (1987) who showed that excess zinc ions could act as competitive inhibitor of carboxypeptidase A.…”
Section: Purification Of Renal Endopeptidase 2416 and Biochemical Chmentioning
confidence: 89%
“…First, zinc ions are required for the enzymatic activities of both proteins; second, excess Zn 2ϩ inhibits both the enzymatic activity of carboxypeptidase and the phosphatase activity of TyrR (25); third, upon adding zinc ion to metal-free apoenzymes, both proteins showed a decrease in fluorescence intensity and a slight change in emission wavelength (14) (Fig. 8); and fourth, both proteins lack cysteine-or histidine-rich regions as identifiable zinc-binding motifs.…”
Section: Discussionmentioning
confidence: 99%